‘Let it stay in the heart’: cultural and gendered experiences of distress among Syrian refugees in Jordan - Lambert, Jessica E.; Abutaleb, Hala; Odeh, Rahaf; de Jong, Joop (Frontiers in Psychology, 2024)
Objective: This qualitative study explored cultural concepts of distress among Syrian refugees in Jordan to inform mental health and psychosocial support services with the population. We sought to understand perceived causes of distress, salient expressions used to describe distress, and ways of coping.Method: Eight focus group discussions (FGDs) were conducted with adult Syrian refugees (four male, four female). Gender-matched Jordanian qualitative researchers facilitated the FGDs. Transcripts were analyzed in Arabic using thematic analysis, validated through a final review of translated data.Four key themes were identified related to participants' experience of distress, perceived causes and consequences, and gender differences (and similarities) in expression and coping. Results also highlighted the complexity of terminology used, and challenges in rank ordering expressions as most salient.Results hold implications for adapting mental health and psychosocial interventions with the population to be more gender sensitive and culturally relevant.